New material of Equus (Amerhippus) neogeus (Mammalia, Perissodactyla) from the late Pleistocene of Olavarría (Argentina) - Prado, Jose Luis (2013)
The fossil mammal locality from the El Polvorín limestone Quarry in Calera Avellaneda (Olavarría, Argentina) is known for its Quaternary mammals. This paper describes new specimens of equids. The comparative study with other horses, from different localities of South America, mostly Argentina and Brazil, allowed identifying the specimen as Equus (Amerhippus) neogeus Lund. This represents a new locality for this species, assigned to the late Pleistocene (Lujanian Stage/Age, c. 130-12 ka BP). The fauna associated with this stratigraphic level is consistent with a lapse of time dominated by fauna adapted to arid and cold conditions.